REPRESENTASI IMIGRAN DALAM STRUKTUR TEMATIK PIDATO VIKTOR ORBAN DAN DONALD TRUMP PADA CPAC 2022-2023 - Harmia, Citra Dewi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
The high migration rate of people from one country to another is supported by the increasingly easy access to mobility available today. This migration phenomenon has attracted controversy because immigrants are often considered a burden on the destination country. This controversy led to various views regarding immigrants, demonstrated through actions and speech. This research aims to show the representation of immigrants found in the thematic development structure in Viktor Orban and Donald Trump's speeches at the 2022-2023 CPAC event. This research uses a descriptive-qualitative method, with data in the form of transcribed speeches from Viktor Orban and Donald Trump. The types of themes that emerge from each clause are then analyzed and classified into marked topical themes and unmarked topical themes. The data analysis results show both speakers' tendency to use unmarked topical clauses with dominant subjects in the form of actors and events. Clauses were found with topical themes related to immigrants, which showed the marginalization of immigrants as a community group with certain stereotypes. However, the representation of immigrants in Donald Trump's speech shows more negative stereotypes than the representation in Viktor Orban's speech.